2017
DOI: 10.2106/jbjs.16.00496
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Patient-Specific Instruments in Total Knee Arthroplasty

Abstract: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
77
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 69 publications
10
77
0
1
Order By: Relevance
“…The results of our study were in line with these observations, similar results concerning the percentage of mTFA outliers had been reported for PSI before [41]. Interestingly, an improvement in the accuracy of the femoral component in PSI has been reported in a meta analysis [16]. Coincident, the risk for tibial malalignment was found to be increased, which is in accordance with the findings of our study, although we did not measure the femoral positioning [16,42].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of our study were in line with these observations, similar results concerning the percentage of mTFA outliers had been reported for PSI before [41]. Interestingly, an improvement in the accuracy of the femoral component in PSI has been reported in a meta analysis [16]. Coincident, the risk for tibial malalignment was found to be increased, which is in accordance with the findings of our study, although we did not measure the femoral positioning [16,42].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, an improvement in the accuracy of the femoral component in PSI has been reported in a meta analysis [16]. Coincident, the risk for tibial malalignment was found to be increased, which is in accordance with the findings of our study, although we did not measure the femoral positioning [16,42]. Yamamura et al reported that in PSI, CT-based 3D-measurements demonstrated vast differences between the preoperative planning of the implants and the actual position of the implants after the operation, particularly for the tibial component [43].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Two recent meta‐analyses enrolled only 9 studies that reported femoral rotation as an outcome, and reached conflicting results: Thienpont et al . concluded that no differences with regard to the rotational alignment are to be expected in the axial plane with the use of PSI, whereas Huijbregts et al . calculated the femoral rotation to be 0.45° more accurate with PSI.…”
Section: Discussionmentioning
confidence: 98%
“…Patient-specific instrumentation has not yet been clearly demonstrated as effective in increasing the accuracy or precision of femoral component rotation: several studies have investigated the effect of PSI on rotational alignment and, with a few exceptions 8,27 , did not find statistical difference with respect to the outliers of femoral component rotation 14,15 and the accuracy in postoperative alignment of femoral rotation [12][13][14]20 . Two recent meta-analyses enrolled only 9 studies that reported femoral rotation as an outcome, and reached conflicting results: Thienpont et al concluded that no differences with regard to the rotational alignment are to be expected in the axial plane with the use of PSI, 28 whereas Huijbregts et al calculated the femoral rotation to be 0.45 more accurate with PSI 9 . Reduction in the number of outliers from target rotational femoral component alignment indicates increased precision: controversial results have been obtained regarding this outcome, with some study groups reporting significant differences in favor of PSI 5,10 and others not 6,7,29 .…”
Section: Discussionmentioning
confidence: 99%